ANALYSIS OF FACILITY QUALITY AT THE TRADITIONAL MARKET TOURIST ATTRACTION OF KRENENG DENPASAR - Putu Wibby Prasetya (Bajang Institute, 2024)
Kreneng Market in Denpasar City has been formally designated as a Cultural Tourist Attraction (DTW) through regional regulations. However, the rapid growth of modern retail confronts this market with the challenge of declining physical tourism amenities. This study aims to systematically measure and evaluate the quality of physical facilities at Kreneng Market from the tourists' perspective to map out revitalization priorities. Utilizing a quantitative descriptive method, data were collected through structured questionnaires from 100 respondents selected via purposive sampling. Data analysis employed descriptive statistics after the questionnaire instrument was declared valid (Sig. < 0.05) and reliable (Cronbach's Alpha = 0.875). The research results indicate that the overall quality of Kreneng Market's facilities falls into the